If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6.5x+12x=-24+11x
We move all terms to the left:
6.5x+12x-(-24+11x)=0
We add all the numbers together, and all the variables
6.5x+12x-(11x-24)=0
We add all the numbers together, and all the variables
18.5x-(11x-24)=0
We get rid of parentheses
18.5x-11x+24=0
We add all the numbers together, and all the variables
7.5x+24=0
We move all terms containing x to the left, all other terms to the right
7.5x=-24
x=-24/7.5
x=-3+1/5
| f(-3)=-3-3 | | -x+3=179 | | -5+7k=-61 | | 8x-41-4×+35=0 | | 396/x-15=-22 | | -10=-4/b | | 36–2w= | | 7x+4=107 | | 36x+25=40+11 | | 2x+2+3x-5+4x-10=41 | | 3t–2(3+t)=–18 | | 8z-2=3z/6 | | 144=2x-5(-2x-12) | | (x)+(x+4)+(3x-9)=90 | | 4+m=93 | | -3x-45=3x+3 | | 3x+7=334 | | 0.5r+6=6.5r | | (7x-30)=(5x+14) | | 5x+2-7=-3 | | 7x/3+5=8.6 | | 5=g+8/8 | | 3v=2v+7 | | 5{x+2}-7=-3 | | 3+2x=7–6x | | 0.15d-2=8 | | 11+3y=53 | | 2/9n+2/2=2/3(n+3) | | -13=9+y | | 4x+10=10x-20 | | 56x=2+7x | | 11-7a=20 |